Beyond Compliance: Integrating Carbon Risk Management for Sustainable Growth in Indonesia - Dedi Haryadi; Hengky Leon; Vito Apriyanto; Ricky Ricky (BIMA Journal (Business, Management, & Accounting Journal), 2026)
Purpose: This study aims to examine the effect of carbon risk on the sustainable growth rate (SGR) of non-financial companies listed on the Indonesia Stock Exchange during 2021–2024. The research is important as climate-related risks increasingly influence corporate sustainability and long-term performance, particularly in emerging markets. Methodology: The methodology employs a quantitative approach using purposive sampling, resulting in 138 firms (552 firm-year observations). Data were analyzed using regression with Robust Least Squares (RLS) to address heteroscedasticity. Results: The results show that carbon risk has a negative and significant effect on sustainable growth, indicating that higher carbon emissions reduce firms’ growth potential. Additionally, financial performance indicators—ROA, DER, TATO, and firm size—positively influence SGR. Findings: The findings highlight that carbon risk not only affects financial stability but also constrains long-term corporate growth. Novelty: The novelty of this study lies in linking carbon risk directly to sustainable growth rate, a relationship rarely explored in prior literature. Originality: Its originality is reflected in the focus on non-financial firms in Indonesia as a developing country context. Conclusion: In conclusion, effective carbon risk management is crucial for sustaining corporate growth. The study provides implications for policymakers and managers to strengthen environmental strategies and reporting practices. Type of Paper: Research article